2019
DOI: 10.21608/ejabf.2019.57921
|View full text |Cite
|
Sign up to set email alerts
|

Feeding on phytoplankton profile of two African Cichlids in large reservoir, Lake Nasser, Egypt

Abstract: This study was carried out in 2016 to investigate the feeding on phytoplankton profile of the Nile tilapia (Oreochromis niloticus) and mango tilapia (Sarotherodon galilaeus) inhabiting Lake Nasser, and its relation to their fisheries biological parameters. Phytoplankton Preference index (PPI), Index of Relative Importance (IRI), and Straus Linear index were used to investigate the feeding patterns of the two species in the lake. Moreover, some fish biological parameters of the two species were determined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
6
10
0
Order By: Relevance
“…This indicated that the fish was a phytoplanktivorous or herbivorous feeder. These findings are supported well by earlier findings that have classified O. niloticus as herbivorous that favor phytoplankton species [38,14,2,19] . Phytoplanktivorous or herbivorous feeding habits of O. niloticus have also been reported in Ethiopian water bodies such as Lake Chamo [38] , Koka Reservoir [14] and Lake Hayq [4] .…”
Section: Food and Feeding Habits Of O Niloticussupporting
confidence: 92%
See 4 more Smart Citations
“…This indicated that the fish was a phytoplanktivorous or herbivorous feeder. These findings are supported well by earlier findings that have classified O. niloticus as herbivorous that favor phytoplankton species [38,14,2,19] . Phytoplanktivorous or herbivorous feeding habits of O. niloticus have also been reported in Ethiopian water bodies such as Lake Chamo [38] , Koka Reservoir [14] and Lake Hayq [4] .…”
Section: Food and Feeding Habits Of O Niloticussupporting
confidence: 92%
“…GIIi index treats each dietary metric equally and some prey items were better represented by %N (e.g., smaller but countable prey) whereas others were better represented by %V (e.g., fish and other larger prey). Phytoplankton preference index (PPI) was determined using percentage frequency of occurrence through the following equation described by Chrisafi et al [11] and Hussian et al [19] .…”
Section: Stomach Content Analysismentioning
confidence: 99%
See 3 more Smart Citations